A Photographic Investigation of Saturated Nucleate Boiling - Anderson, Douglas L. (My University, 1969)
This thesis describes a photographic investigation of saturated nucleate boiling. Five different fluids were boiled on an oxide coated glass surface at various levels of heat flux. The nature of the boiling surface was such that the boiling phenomenon could be photographed through the surface from below. Active nucleation sites were identified and counted by analysis of still photographs obtained using this technique. Active nucleation site density data obtained from the analysis was correlated with surface temperature using the Gaertner site activation theory which requires the use of two arbitrary constants No and o. It is demonstrated that for the particular surface used, the product irrespective of the fluid boiled so that the relationship. satisfactorily predicts the active nucleation site density.
Document is missing page 93.
Keywords: Mechanical Engineering; Mechanical Engineering